Sosialisasi Pencegahan Pernikahan Dini - Rusli, Nurfadillah; Nurwahidah, Nurwahida; Eril, Eril; Surianti, surianti; Melati , Rahma (INKAMKU : Journal of Community Service, 2024)
The service program activities were carried out at UPTD SMPN 15 Sinjai, Sinjai Tengah sub-district, Samaenre sub-district by holding an early marriage seminar. Early marriage is a marriage carried out by children under 19 years of age for women and under 21 years of age for men. As is the case in Samaenre Village, Central Sinjai District, Sinjai Regency, early marriages always occur, resulting in the Village Government having to minimize the number of early marriages. Internal factors come from within, namely the wishes of the individual himself, while external factors are parents' economic factors, educational factors. , and parental factors or the wishes of the parents. Many teenagers are trapped in young marriages, especially those from underprivileged families, so they choose to marry at a young age to reduce the family's economic burden. There are many possible risks to early marriage, both physical and psychological risks. Therefore, to prevent early marriage, the author took the initiative to hold early marriage seminars.